Secrets - Steel, Danielle (London : Sphere, 2010)
When Manhattan was conceived as a new TV series it offered more than just the chance for a network to make the ratings. For the stars involved it meant the chance of a lifetime - if they were prepared to pay the price.
Keywords: Television actors and actresses -- Fiction; Love stories